Desenvolvimento tecnológico e caracterização de biscoito de semente de umari (Poraqueiba sericea Tulasne) e mel de abelhas-sem-ferrão - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2026)
The development of new products from Amazonian fruits and honey represents an important contribution to the advancement of fruit growing and meliponiculture in the state of Amazonas. Among the highlighted products are umari (Poraqueiba sericea Tulasne) and stingless bee honey (NSB). Umari is a tropical fruit whose mesocarp surrounds a seed that represents approximately 74.0% of the fruit and has a hazelnut-like aroma. Honey, a widely known product, has high nutritional value and is produced by bees of the Meliponina subgroup. For the characterization of the cookie formulations, the endosperm was removed from the seed and subjected to decantation in distilled water for 72 hours, with daily water changes, to eliminate bitterness. After this process, the material was filtered, oven-dried at 50 °C, ground, and analyzed for proximate composition. The cookies were prepared using umari seed flour, ASF honey, and butter. Formulation A (FA) received an addition of wheat flour, while formulation B (FB) used fine rolled oats. The resulting flour showed fine texture, pink coloration, and a composition of 0.5% ash, 7.5% moisture, 0.5% lipids, 5.3% proteins, 86.2% carbohydrates, and an energy value of 370.5 kcal. For the cookies, FA presented 0.5% ash, 7.3% moisture, 12.0% lipids, 4.4% proteins, and 75.7% carbohydrates. FB presented 0.9% ash, 6.0% moisture, 13.6% lipids, 5.4% proteins, and 74.0% carbohydrates. The lowest scores in the sensory analysis were observed for the texture attribute (FA = 5.93; FB = 5.97), while appearance received the highest evaluations (FA = 7.27; FB = 6.93). Regarding purchase intention, 40.9% of consumers stated that they would probably buy both formulations. Thus, the product is rich in carbohydrates and vegetable lipids, representing a nutritionally adequate alternative for human consumption.
Keywords: Abelhas; Frutos amazônicos; Farinha; Tecnologia de alimentos; CIENCIAS DA SAUDE: NUTRICAO; .; .; .